Metropolita Andrzej Szeptycki wobec wyzwań historyczno-eklezjalnych - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2010)
The study presents selected aspects of the pastoral and writing output of Metropolitan Andrey Sheptytsky. Obviously, they do not encompass or exhaust the complete range of his activity and genuine achievements during his ministry in the Greek Catholic Church. But it was not the purpose of this study to list all the accomplishments or to emphasize the general effect of the works of this outstanding hierarch of the Church. The overriding reason for bringing out Sheptytsky’s profile was the attempt to show him against the background of his epoch and its specific historical-religious circumstances, in order to draw attention to his stance as a person and Church hierarch in the context of essential historical challenges. The following issues are tackled: Sheptytsky’s impact on the shaping of organizational and spiritual matters of his Church, his initiation of the movement of renewal of the Eastern rite in the Eastern Catholic Church, his openness to cooperation and strengthening relations within the Christian communities. Last but not least, the author wished to accentuate the personal authenticity of the Metropolitan, who has not always been assessed in a reliable and objective way.